KOREKSI KETIDAKMERATAAN PENCAHAYAAN PADA CITRA MIKROSKOP DIGITAL - , NURWANTO YOGI SUTARI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Image as the result from observation with microscope sometimes incompatible with the conditions of the object being obeserved. Many digital images have the effect of uneven illumination that looks like bright in the middle and dark at the edge, and there are background that contain different color than the other so it is not look uniform. Uneven illumination effect will cause problem and disrupt the process of analysis when it is done for further image processing, such as segmentation using thresholding and image merging. Correction process using smoothing method is carried out on 3 types of image, that is background image, image with little object and image with many object or blood cell images. All of these types will be corrected on a program that has been created. The program has 3 variables that can be varied, namely Ï1, Ï2, Î³ and 3 channels namely hue, saturation, value. Variable Ï1 and Ï2 is the standard deviation of Gaussian function, while variable Î³ is a factor that affects the value of intensity maping between the input image with the output image. Correction process is done by changing 3 variables and 3 channels that appropriate to obtain minimum value of standard deviation. The result show that image in digital microscope successfully corrected but reduce some information, such as differences in color composition. The success rate of image correction that used in this research are 68% for background image, 56,9% for image with little object, and 39,3% for image with many object or blood cells image. Keyword : correction, uneven illumination, smoothing, digital microscope, digital image